Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Sure, let's factor [tex]\(64x^6 - 27\)[/tex] using the identity for the difference of cubes:
[tex]\[a^3 - b^3 = (a - b)\left(a^2 + ab + b^2\right).\][/tex]
First, we need to express the given expression [tex]\(64x^6 - 27\)[/tex] in terms of cubes. Let’s identify [tex]\(a\)[/tex] and [tex]\(b\)[/tex] such that [tex]\(a^3 = 64x^6\)[/tex] and [tex]\(b^3 = 27\)[/tex].
Now, let's break it down step-by-step:
1. For [tex]\(64x^6\)[/tex] to be a cube, we note that [tex]\(64 = 4^3\)[/tex] and [tex]\(x^6 = (x^2)^3\)[/tex]. Therefore, we can write:
[tex]\[64x^6 = (4x^2)^3.\][/tex]
So, [tex]\(a = 4x^2\)[/tex].
2. For 27 to be a cube, we recognize that:
[tex]\[27 = 3^3.\][/tex]
So, [tex]\(b = 3\)[/tex].
Now, we have identified [tex]\(a\)[/tex] and [tex]\(b\)[/tex] as follows:
[tex]\[ \begin{array}{l} a = 4x^2 \\ b = 3 \end{array} \][/tex]
Hence, the expression [tex]\(64x^6 - 27\)[/tex] can be rewritten using the difference of cubes formula as:
[tex]\[64x^6 - 27 = (4x^2)^3 - 3^3 = (4x^2 - 3)\left((4x^2)^2 + (4x^2)(3) + 3^2\right).\][/tex]
[tex]\[a^3 - b^3 = (a - b)\left(a^2 + ab + b^2\right).\][/tex]
First, we need to express the given expression [tex]\(64x^6 - 27\)[/tex] in terms of cubes. Let’s identify [tex]\(a\)[/tex] and [tex]\(b\)[/tex] such that [tex]\(a^3 = 64x^6\)[/tex] and [tex]\(b^3 = 27\)[/tex].
Now, let's break it down step-by-step:
1. For [tex]\(64x^6\)[/tex] to be a cube, we note that [tex]\(64 = 4^3\)[/tex] and [tex]\(x^6 = (x^2)^3\)[/tex]. Therefore, we can write:
[tex]\[64x^6 = (4x^2)^3.\][/tex]
So, [tex]\(a = 4x^2\)[/tex].
2. For 27 to be a cube, we recognize that:
[tex]\[27 = 3^3.\][/tex]
So, [tex]\(b = 3\)[/tex].
Now, we have identified [tex]\(a\)[/tex] and [tex]\(b\)[/tex] as follows:
[tex]\[ \begin{array}{l} a = 4x^2 \\ b = 3 \end{array} \][/tex]
Hence, the expression [tex]\(64x^6 - 27\)[/tex] can be rewritten using the difference of cubes formula as:
[tex]\[64x^6 - 27 = (4x^2)^3 - 3^3 = (4x^2 - 3)\left((4x^2)^2 + (4x^2)(3) + 3^2\right).\][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.